(untitled) (Malaysian Management Journal, 1997)
The structure of the semiconductor industry has been changing recently. Japanese companies have lost their competitiveness, while their US and Korean counterparts have been strengthening theirs. At the same time, the map of the inter-firm relationships in the IT industry is changing. Patterns of strategic alliances in the semiconductor business have been evolving and have become complicated. We will investigate the transformation of strategic alliances, and we will propose how Japanese semiconductor companies can recover through a new type of alliance.